2020
DOI: 10.1007/s13203-020-00246-8
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Ce–Zr mixed oxides for selective oxidation of styrene in liquid phase

Abstract: This work reports the synthesis of mesoporous Ce1-x-ZrxO2-δ (x = 0.5 and 0.8) mixed oxides with distinct Ce/Zr mole ratio by inverse micelle template method and their catalytic exploration for epoxidation of styrene in isopropanol solvent using TBHP as the oxidant. Among various catalysts investigated, the Ce0.8Zr0.2O2 combination catalyst exhibited best catalytic activity with ~ 98% conversion and ~ 90% selectivity to styrene epoxide. The synthesized Ce–Zr mixed oxide catalysts were characterized by various s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The V 2 O 5 sample displays characteristic Raman peaks at 1000, 708, 488, 411, 290, and 151 cm À1 . 35 The contents of Ce and V elements of the synthesized catalysts were analyzed by ICP-OES analysis, as shown in Table 2. The obtained results are close to calculated metal ratio in the preparation of catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The V 2 O 5 sample displays characteristic Raman peaks at 1000, 708, 488, 411, 290, and 151 cm À1 . 35 The contents of Ce and V elements of the synthesized catalysts were analyzed by ICP-OES analysis, as shown in Table 2. The obtained results are close to calculated metal ratio in the preparation of catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The powder was washed with absolute ethanol, centrifuged, and dried in an electrical oven overnight at 120 °C. Finally, the synthesized compound was subjected to calcination cycles at different temperatures in an air atmosphere of 150 °C for 12 h, 250 °C for 6 h, 350 °C for 4 h, 450 °C for 2 h, and 550 °C for 1 h. 35…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPR profile of ceria shows two major peaks, the peak at lower temperatures (∼522.4 °C) is related to surface-capping oxygen reduction and the peak at higher temperatures (∼786.8 °C) is due to bulk ceria reduction. 25,27 It is observed that the TPR peaks of bismuth-doped ceria are shifted to lower temperature regions compared to those of pure CeO 2 . This observation indicates the change in the redox properties of ceria after doping with bismuth in ceria.…”
Section: Resultsmentioning
confidence: 99%
“…Previously a variety of transition metal (like Mn, Co, Fe, and Zr)-doped catalysts were developed for various oxidation reactions involving soot, 24 hydrocarbons, 25 alcohols, 26 etc. In our recent study, a mesoporous Ce-Zr mixed oxide 27 catalyst exhibited 98% conversion and 90% styrene epoxide selectivity with TBHP as the oxidant.…”
Section: Introductionmentioning
confidence: 95%